Multi-strain probiotics alleviate loperamide-induced constipation by adjusting the microbiome, serotonin, and short-chain fatty acids in rats - Jeong, Jin-Ju; Ganesan, Raja; Jin, Yoo-Jeong; Park, Hee Jin; Min, Byeong Hyun; Jeong, Min Kyo; Yoon, Sang Jun; Choi, Mi Ran; Choi, Jieun; Moon, Ji Hyun; Min, Uigi; Lim, Jong-Hyun; et al. (Frontiers in Microbiology, 2023)
Constipation is one of the most common gastrointestinal (GI) disorders worldwide. The use of probiotics to improve constipation is well known. In this study, the effect on loperamide-induced constipation by intragastric administration of probiotics Consti-Biome mixed with SynBalance® SmilinGut (Lactobacillus plantarum PBS067, Lactobacillus rhamnosus LRH020, Bifidobacterium animalis subsp. lactis BL050; Roelmi HPC), L. plantarum UALp-05 (Chr. Hansen), Lactobacillus acidophilus DDS-1 (Chr. Hansen), and Streptococcus thermophilus CKDB027 (Chong Kun Dang Bio) to rats was evaluated. To induce constipation, 5 mg/kg loperamide was intraperitoneally administered twice a day for 7 days to all groups except the normal control group. After inducing constipation, Dulcolax-S tablets and multi-strain probiotics Consti-Biome were orally administered once a day for 14 days. The probiotics were administered 0.5 ml at concentrations of 2 × 108 CFU/mL (G1), 2 × 109 CFU/mL (G2), and 2 × 1010 CFU/mL (G3). Compared to the loperamide administration group (LOP), the multi-strain probiotics not only significantly increased the number of fecal pellets but also improved the GI transit rate. The mRNA expression levels of serotonin- and mucin-related genes in the colons that were treated with the probiotics were also significantly increased compared to levels in the LOP group. In addition, an increase in serotonin was observed in the colon. The cecum metabolites showed a different pattern between the probiotics-treated groups and the LOP group, and an increase in short-chain fatty acids was observed in the probiotic-treated groups. The abundances of the phylum Verrucomicrobia, the family Erysipelotrichaceae and the genus Akkermansia were increased in fecal samples of the probiotic-treated groups. Therefore, the multi-strain probiotics used in this experiment were thought to help alleviate LOP-induced constipation by altering the levels of short-chain fatty acids, serotonin, and mucin through improvement in the intestinal microflora.